Analysis of the hydrological disaster occurred in the state of Rio Grande do Sul, Brazil in September 2023: Vulnerabilities and risk management capabilities - Célia dos Santos Alvalá, Regina [UNESP]; Ribeiro, Daniela Ferreira; Marengo, Jose Antonio [UNESP]; Seluchi, Marcelo Enrique; Gonçalves, Demerval Aparecido; Antunes da Silva, Larissa; Cuartas Pineda, Luz Adriana [UNESP]; Saito, Silvia Midori [UNESP] (Elsevier, 2024)
Understanding disaster risk in all its dimensions is a priority on global agendas. This study developed an integrated analysis of flood risk drivers using a methodology based on meteorological and hydrological analyses, population vulnerability assessment, and municipal risk management capabilities from public data sources. Rio Grande do Sul, Brazil, was selected due to extreme rainfall that affected more than 400,000 people in September 2023. The results showed that a stationary frontal system caused unprecedented rain and floods between September 1 and 4, 2023. A quasi-stationary cold front from Argentina intensified precipitation, exacerbated by an upper-level low-pressure area. Attributed to the 2023 El Niño, these events resulted in heavy rainfall exceeding normal levels by 200–300 mm, leading to floods that affected 107 municipalities, resulting in 54 deaths and extensive property damage. The Caí and Taquari-Antas river basins were particularly affected, with river levels exceeding critical limits, causing severe floods and most deaths. Vulnerability was higher among populations of low socioeconomic status living in housing with precarious infrastructure, especially in small municipalities dependent on agriculture. The high vulnerability is due to the lack of public policies that improve socioeconomic conditions, such as social action policies for agricultural workers, combating educational delays, and improvements in household infrastructure. Furthermore, municipal administrations must invest in strengthening tools, actions, and policies focused on risk response and management, and promoting educational activities in civil protection and defense, with special attention to the elderly population.
Keywords: Disaster risk management; Extreme weather events; Hydrometeorological risks; Vulnerability assessment